Diagnostic Workup of Neonates With Esophageal Atresia: Results From the EUPSA Esophageal Atresia Registry - Morini, Francesco; Conforti, Andrea; Zani, Augusto; Sindjic-Antunovic, Sanja; Koivusalo, Antti; Friedmacher, Florian; van Heurn, Ernest; Pierro, Agostino; Hollwarth, Michael; Bagolan, Pietro (Frontiers in Pediatrics, 2020)
Aim: Controversies exist on the optimal diagnostic workup for neonates with esophageal atresia (EA) with/without tracheoesophageal fistula (TEF). Aim of this study was to describe the current diagnostic policies in EA/TEF patients enrolled in an International multicenter registry. Methods: All patients consecutively registered from July 2014 to December 2017 in the EUPSA Esophageal Atresia Registry (EUPSA-EAR) were included in the study. Data related to diagnostic investigations among Centres forming the EUPSA-EAR were analyzed. Chi-square test or Fisher’s exact test were used as appropriate. Main results: During the study period, 374 consecutive patients were recorded by 23 Centers. The majority of patients underwent chest X rays, echocardiography, abdominal ultrasound, and abdominal X rays. Preoperative bronchoscopy and esophageal gap measurement were performed in one third of the patients. Conclusions: Present data from a large cohort of patients from the EUPSA- EAR show both inter-institutional and intra-institutional variability in diagnostic workup of patients with EA/TEF. Efforts should be made to develop guidelines on the diagnostic workup for EA/TEF patients.